Auditory P300 study in patients with convalescent bipolar depression and bipolar depression. Issue 11 (1st August 2018) - Fu, Linyan; Xiang, Dan; Subodh, Dahal; Xiao, Jiawei; Yao, Lihua; Wang, Ying; Wang, Huiling; Wang, Gaohua; Liu, Zhongchun
Abstract : The aim of this study was to investigate the information-processing changes during an auditory oddball task among healthy controls (HCs), convalescent bipolar depression (BPC), and bipolar depression (BPD) patients. Thirty patients with BPD, 27 patients with BPC, and 30 HC were recruited in this study. The participants' performance (reaction time and accuracy) as well as P300 amplitude and latency during the tests were analyzed statistically. BPD and BPC showed poor task performance compared with HC. BPD had lower P300 amplitude and delayed P300 latency in the frontal, central, and parietal areas than HC. BPC had lower P300 amplitude, but no difference in P300 latency compared with the HC group. Further, P300 latency was significantly delayed over the right relative to the left region. In conclusion, bipolar patients had P300 abnormalities and deficits in cognitive processing of stimulus, and may be present even when emotional symptoms were relieved.